Development and evaluation of Mustard green pickled liquid as starter for Morinda citrifolia Linn. Fermentation - S. Sirilun (2018)
© All Rights Reserved. The selection of starter culture for preparing fermented plant beverages influences the entire production and quality of the product. The traditional way of naturally fermented mustard green pickled liquid (MGPL) has been used in northern Thailand for several decades, and the fermented Morinda citrifolia Linn. fruit juice is one of the primary fermented plant beverages. The current study explored the use of MGPL as a starter for the fermentation of M. citrifolia fruit. The MGPL was preparing as per the traditional procedure and used at a different concentration in the various formula of M. citrifolia fruit fermentation (MFR). Moreover, the influence of raw onion extract (ROE) in MFR has also been evaluated. The pH of the MGPL (6.5 ± 0.2 to 3.8 ± 0.1) and MFR was progressively reduced during fermentation. The physiochemical and microbiological analysis of MGPL and MFR suggested that the content of organic acids were increased upon fermentation, especially the recipes with heavy inoculation (15%) of MGPL starter. The total bacterial load, coliforms, Lactobacillus, yeast and mold levels were in acceptable range in naturally fermented MGPL. All the MFR recipes are microbiologically safe and enriched with Lactic acid bacteria. The ethanol content in MGPL (0.6348 ± 0.02% V/V) and MFR recipes (ranging from 0.5524 ± 0.02 to 0.9677 ± 0.04% V/V) were slightly higher than the permissible level of Thai commercial product standards (≥ 0.5%), whereas the methanol content was in acceptable level (≤ 240 ppm). The reducing sugar level in MFR recipes were gradually decreased due to the fermentation. In conclusion, the MGPL is considered as a safe starter for MFR with ROE supplementation. Hence, additional studies are recommended on traditional formulations and its applications in modern food technology, especially in the production of fermented plant beverages.